Improving comfort around dying in elderly people: a cluster randomised controlled trial. Issue 10090 (8th July 2017) - Beernaert, Kim; Smets, Tinne; Cohen, Joachim; Verhofstede, Rebecca; Costantini, Massimo; Eecloo, Kim; Van Den Noortgate, Nele; Deliens, Luc
Summary: Background: Over 50% of elderly people die in acute hospital settings, where the quality of end-of-life care is often suboptimum. We aimed to assess the effectiveness of the Care Programme for the Last Days of Life (CAREFuL) at improving comfort and quality of care in the dying phase in elderly people. Methods: We did a cluster randomised controlled trial in acute geriatric wards in ten hospitals in Flemish Region, Belgium, between Oct 1, 2012, and March 31, 2015. Hospitals were randomly assigned to implementation of CAREFuL (CAREFuL group) or to standard care (control group) using a random number generator. Patients and families were masked to interventaion allocation; hospital staff were unmasked. CAREFuL comprised a care guide for the last days of life, training, supportive documentation, and an implementation guide. Primary outcomes were comfort around dying, measured with the End-of-Life in Dementia–Comfort Assessment in Dying (CAD-EOLD), and symptom management, measured with the End-of-Life in Dementia–Symptom Management (SM-EOLD), by nurses and family carers. Analyses were by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT01890239 . Findings: 451 (11%) of 4241 beds in ten hospitals were included in the analyses. Five hospitals were randomly assigned to standard health care practice and five to the CAREFuL programme; 118 patients in the control group and 164 in the CAREFuL group were eligible for assessment. Assessments were done for 132 (80%) of 164 patients in the CAREFuL group and 109 (92%) of 118 in the control group by nurses, and 48 (29%) in the CAREFuL group and 23 (19%) in the control group by family carers. Implementation of CAREFuL compared with control significantly improved nurse-assessed comfort (CAD-EOLD baseline-adjusted mean difference 4·30, 95% CI 2·07–6·53; p<0·0001). No significant differences were noted for the CAD-EOLD assessed by family carers (baseline-adjusted mean difference −0·62, 95% CI −6·07 to 4·82; p=0·82) or the SM-EOLD assessed by nurses (−0·41, −1·86 to 1·05; p=0·58) or by family carers (−0·59, −3·75 to 2·57; p=0·71). Interpretation: Although a continuous monitoring of the programme is warranted, these results suggest that implementation of CAREFuL might improve care during the last days of life for patients in acute geriatric hospital wards. Funding: The Flemish Government Agency for Innovation by Science and Technology and the Belgian Cancer Society "Kom Op Tegen Kanker".